Vesicoureteral reflux of a solitary kidney treated with endoscopic injection therapy comprising tandem injections administered with the assistance of a ureteral guidewire in a young girl - Tetsuji Maruyama; Kentaro Mizuno; Hidenori Nishio; Daisuke Matsumoto; Takuya Sakata; Yutaro Hayashi (Urology Case Reports)
We present the case of a 12-year-old girl with vesicoureteral reflux (VUR) of a solitary kidney treated using a modified hydrodistention implantation technique. A needle was set parallel to the ureteral guidewire inserted through the ureteral orifice before performing injections to correct VUR. Multi-site tandem injections were administered along the wire, which confirmed the direction and length of the ureteral tunnel. The mounds were aligned without ureteral kinking. A reduced volume of dextranomer-hyaluronic acid copolymer (Deflux®) was required to construct an effective anti-reflux tunnel. A voiding cystourethrogram confirmed VUR resolution. This technique avoided complications associated with a solitary kidney.